1993
DOI: 10.1017/s0952523800004776
|View full text |Cite
|
Sign up to set email alerts
|

Subcortical connections of subdivisions of inferior temporal cortex in squirrel monkeys

Abstract: On the basis of cortical connections and architectonics, inferior temporal (IT) cortex of squirrel monkeys consists of a caudal, prestriate-recipient region, ITC; a rostral region, ITR; and possibly an intermediate region along the border of ITC and ITR, ITI (Weller & Steele, 1992). ITC contains dorsal (ITCd) and ventral (ITCv) areas. The subcortical connections of these subdivisions of IT cortex were determined in the present study from the results of cortical injections of wheat-germ agglutinin conjugate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 113 publications
7
52
0
Order By: Relevance
“…43 for evidence that this version of the concurrent visual-discrimination task, like the 24-h ITI version, is insensitive to the effects of medial temporal damage). Taken together with the anatomical connectional evidence (9)(10)(11)(12)(13)(33)(34)(35)(36), these several different patterns of lesion-induced deficit support the proposal (29,30) that long-term visual learning and memory are mediated by at least two parallel pathways diverging from a common source, with a TE-limbic projection forming part of a neural circuit critical for visual recognition and a TE-neostriatal projection comprising part of a circuit mediating visual habit formation. (As indicated at the outset, a third projection from TE to the inferior prefrontal convexity seems to be part of yet another circuit, this one serving short-term visual memory.…”
Section: Discussionsupporting
confidence: 65%
“…43 for evidence that this version of the concurrent visual-discrimination task, like the 24-h ITI version, is insensitive to the effects of medial temporal damage). Taken together with the anatomical connectional evidence (9)(10)(11)(12)(13)(33)(34)(35)(36), these several different patterns of lesion-induced deficit support the proposal (29,30) that long-term visual learning and memory are mediated by at least two parallel pathways diverging from a common source, with a TE-limbic projection forming part of a neural circuit critical for visual recognition and a TE-neostriatal projection comprising part of a circuit mediating visual habit formation. (As indicated at the outset, a third projection from TE to the inferior prefrontal convexity seems to be part of yet another circuit, this one serving short-term visual memory.…”
Section: Discussionsupporting
confidence: 65%
“…Similar results were reported by Bazier, et al (1993) and Webster et al (1993), with some additional involvement of PIcl with TEO injections. In squirrel monkeys, injections in a caudal IT region, ITc (comparable to TEO), labeled neurons in PLvl and PIcl, but also in PIp (Steele and Weller, 1993). The neurons labeled in PIp may have resulted from the injection also involving rostral IT, where injections labeled PIp, PLdm, and PM.…”
Section: Pulvinar Connections With Cortical Areas Of the Ventral Streammentioning
confidence: 93%
“…Subsequent studies led to some modification of the border of DL, and to the subdivision of DL into rostral and caudal areas, DLr and DLc, containing parallel retinotopic representations and differing in connection patterns (Cusick and Kaas, 1988;Steele and Weller, 1993). The rostral area, DLr has cortical connections that associate it with the dorsal stream while the caudal division has connections predominantly with the ventral stream.…”
Section: Cortical Areas Of the Dorsal And Ventral Streamsmentioning
confidence: 99%
“…Previous studies have shown that the posterior part of the caudate nucleus and the posteroventral putamen participate in VD and object discrimination tasks (Battig et al, 1960;Divac et al, 1967;Buerger et al, 1974). These striatal regions receive projections from the inferotemporal cortex (Saint-Cyr et al, 1990;Steele and Weller, 1993;Webster et al, 1993;Yeterian and Pandya, 1995), further suggesting that they are parts of a network involved in visual associative memory. The absence of increase in the tail during the VD task may be explained by the fact that neurons responding to physical patterns of visual stimuli in the tail rapidly habituate and may not respond after several (one to eight) presentations of the same stimuli (Caan et al, 1984).…”
Section: Corticostriatal Network For Working and Associative Memoriesmentioning
confidence: 95%